The Influence of Social Media on The Self – Esteem of Youth: Special Reference to Facebook - Pothanayaki, N.; Anutharsi, G.; Poongulaly, S. (My University, 2017)
In this post – metaphysical age youths are pulled or pushed into a world of illusion created by virtual reality such as Facebook, Instagram, Twitter, Linked in, Tumbler, YouTube, Blog and etc., because it has the foremost influence on the self- esteem – an individual’s overall personalized emotional evaluation of his or her own worth – of youth whose use of social media has multiplied in recent years. This study investigates the connection between Facebook (as preferred example for Social media) media, and the positive cum, negative impacts on the self-esteem of youth. The “ideal image”, as propagated by Facebook is seen as the scale and if youths are incapable to get to that ‘ideal image’, they feel that they are not so good for anyone or even for themselves but at that same time this perpetual exposure to ‘ideal’ gives a space for them to upswing their self-esteem. Facebook impacts their self-esteem within themselves and at the society level too. Also it helps them to become a well-known person in the social media platforms. By upgrading their self-esteem, they try to create an optimistic image and inspire others to like themselves. The study concludes, that Facebook brings a powerful sense of achievement and public recognition towards youth in order to enhance their self – esteem, which can be also seen as a mistaken identity that emanates from simulacrum creating a hyper reality due to the interactions, the virtual reality created on social media sites by shallow minded people.
Keywords: Social Media; Facebook; Self-Esteem; Ideal Image; Youth; Positive and Negative influence